Readings in public sector economics - Baker, Samuel H.; Elliot, Catherine S. (Lexington, Mass. : D.C. Heath, 1990)
Perspectives on economics and the public sector. Economics of externalities. Economics of public goods. Economics of the political process. Economics of taxation. Economics of fiscal federalism.
Keywords: Finance; Economics; Finance, Public